A CASE REPORT: CHALLENGES IN THE MANAGEMENT OF TOXIC MULTI NODULAR THYROID IN PREGNANCY WHO HAD CRISIS THYROID - Kurnia Alisaputri; Sony Wibisono (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Managing crisis thyroid in toxic multi nodular thyroid in pregnancy is challenging. This case objective is to highlight comprehensive treatment going to safe mother & baby’s life. A woman, 43 years old in 13th week of her third pregnancy, admitted in emergency room with palpitating and vomiting as her chief complaints. Her complaints had started since she stopped taking propylthiouracyl. She used to take it since diagnosed hyperthyroid. She was diagnosed crisis hyperthyroid in pregnancy. The first main goal was to stabilize the patient, curing the precipitate factors, and assist her to have a healthy baby. She was discharged from hospital day 7th. She was routinely checked FT4 for evaluation and switch on Thyrozol during 25-26th weeks and continued it until postpartum. Her baby was delivered vaginally with normal APGAR score and growing well. Based on her experience, she agreed to have IUD to prevent unplanned pregnancy.